Social support and at risk sexual behavior in adolescents of Lebrija-Santander - Orcasita, Linda Teresa (2012)
This study examined social support and sexual risk behavior in adolescents attending an educational institution in the municipality of Lebrija Santander. The sample involves 359 teenagers aged 12-18. This is a non-experimental descriptive-correlational study. Measures included a series of questionnaires, involving Risk Behavior Surveillance (YRBS), and the MOS Questionnaire Family APGAR. Results show that teens who started their sexual life, are at risk of sexual behaviors such as: non-condom use, alcohol consumption and the onset of sexual life at an early age. Also young people who have started their sexual life are those who perceive less emotional and instrumental support from their primary support network (family). It concludes on the need to strengthen support networks of adolescents, because they are directly related to sexual risk behavior is taken by people, is important to involve not only young people but also the involvement of parents, institutions education, teachers, among others, programs designed sexual and reproductive health for adolescents.